The Loves of Others: Autoethnography and Reflexivity in Researching Distance Relationships - Holmes, Mary (Qualitative Sociology Review, 2010)
Reflexive accounts of research are important, but they should include attention to a wider range of relations than those between researcher and participant. The researcher’s position in relation to the participants does merit discussion, especially when there is an element of autoethnography involved. However, assistants in the research such as transcribers, can play a role in accounting for the research. The relationships participants have with loved ones also shape how they reflexively account for themselves and their experiences, in this case – of being in a distance relationship.